Flexible Gas Sensors: Glass‐Fabric Reinforced Ag Nanowire/Siloxane Composite Heater Substrate: Sub‐10 nm Metal@Metal Oxide Nanosheet for Sensitive Flexible Sensing Platform (Small 44/2018). Issue 44 (5th November 2018) - Jang, Ji‐Soo; Lim, Young‐Woo; Kim, Dong‐Ha; Lee, Daewon; Koo, Won‐Tae; Lee, Hyunhwan; Bae, Byeong‐Soo; Kim, Il‐Doo
Abstract : In article number1802260, Byeong‐Soo Bae, Il‐Doo Kim, and co‐workers describe a highly sensitive, flexible sensing platform that employs Pt‐loaded SnO2 nanosheets (Pt‐SnO2 NSs) and an Ag nanowires embedded glass‐fabric reinforced hybrimer heater substrate. The ultrathin Pt‐SnO2 NSs‐loaded flexible heater substrate offers not only high mechanical stability but also a superior response towards 1 ppm dimethyl sulfide gas with exceptional selectivity.